Skull Vault Morphology in Subdural Hematomas: A Geometrical Analysis - Khursheed, Nayil; Jain, Ashish; Haneef, Muhammad; Tanki, Humam; Ramzan, Altaf; Shaheen, Feroze; Wani, Abra (Indian Journal of Neurotrauma, 2015)
Background The issue of cranial symmetry on the lateralization of chronic subdural hematomas has been raised in the past but not fully settled.Aim The aim of the study was to evaluate the effect of skull morphology on the lateralization of chronic subdural hematomas.Methods We conducted a prospective study in chronic and subacute subdural hematomas over a period of 1 year. All the patients had a CT scan of the head and the relationship of the cranial symmetry with the side of the hematomas was evaluated. We had a total of 138 patients.Results The frontal symmetry was found in 23.18% (32/138) patients and asymmetry in 76.81% (106/138) patients. The occipital symmetry and asymmetry were found in 10.14% (14/138) and 89.85% (124/138) patients, respectively. Bilateral chronic subdural hematomas were more common in craniums that had frontal and occipital symmetry, and unilateral subdural hematomas were more common in craniums that had frontal asymmetry.Conclusion Skull vault morphology has a significant bearing on the bilaterality and the side of the chronic and subacute subdural hematomas. This relationship may have a bearing on the future understanding of the etiopathogenesis of subdural hematomas.
Keywords: subdural hematoma; head injury; skull vault morphology; skull asymmetry